2020
DOI: 10.1002/jcp.29498
|View full text |Cite
|
Sign up to set email alerts
|

ERO1α promotes testosterone secretion in hCG‐stimulated mouse Leydig cells via activation of the PI3K/AKT/mTOR signaling pathway

Abstract: ER oxidoreduclin 1α (ERO1α) is an oxidase, participating in formation of secretory and membrane proteins. However, the other physiological functions ERO1α is not well known. We found that ERO1α is high in the Leydig cells of the testis. Therefore, the purposes of the current study are to explore the role of ERO1α and the possible mechanisms in regulating cell proliferation, apoptosis, and testosterone secretion of Leydig cells. ERO1α was mainly localized in Leydig cells in the adult mice testes by immunofluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…After one week of adaptation to laboratory conditions, the adult mice were used to isolate PLCs following the procedure of our recent study [ 50 ]. Specifically, the testes were excised, collected, and trypsinized with collagenase I (1 mg/mL) at 37 °C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After one week of adaptation to laboratory conditions, the adult mice were used to isolate PLCs following the procedure of our recent study [ 50 ]. Specifically, the testes were excised, collected, and trypsinized with collagenase I (1 mg/mL) at 37 °C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…The sequences of the shRNAs are listed in Table 1 . The process of lentivirus packaging was reported in our previous study [ 50 ]. Briefly, recombinant lentivirus vectors and packaging vectors (pGag/Pol, pRev, and pVSV-G) were co-transfected into HEK 293T cells.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have revealed that the PI3K/AKT/mTOR pathway participates in the biological processes of apoptosis and steroidogenesis in granulosa and Leydig cells (110)(111)(112)(113)(114).…”
Section: Effect Of Bmal1 Deficiency On Signaling Pathways Associated ...mentioning
confidence: 99%
“…The PI3K/NF-kB pathway is also involved in steroidogenesis. NF-kB was demonstrated to participate in circadian rhythm generation and was also associated with the PI3K/AKT/ mTORC1 pathway, which functions in steroid hormone production (110)(111)(112)(113)(114). Female BMAL1-KO mice exhibited impaired steroidogenesis and activated phosphorylation of the PI3K/NF-kB pathway.…”
Section: Effect Of Bmal1 Deficiency On Signaling Pathways Associated ...mentioning
confidence: 99%
“…The PI3K/AKT signaling pathway has been shown to play an important role in steroidogenic cell development, function, and apoptosis (51)(52)(53). To examine whether this signaling pathway is affected by midazolam treatment, the protein expression levels and phosphorylation of the two key components in the pathway, AKT and CREB, were analyzed by Western blotting (Figure 8).…”
Section: Effect Of Midazolam On Akt-creb Signaling Pathwaymentioning
confidence: 99%